Factors effecting bank selection views from the customer's perspective - A.Rahim, Muhammad Amirul Ardy (2014)
Purpose – The purpose of the study is to identify the relationship between reliability,accessibility and convenience towards the customer choice of conventional bank. Another purpose is to identify the most influence factor that affect the customer choice of conventional bank. Design/methodology/approach – In order to gain the data, questionnaire is constructed and distributed using simple random sampling method that consists of 100 respondents in Pasir Gudang, Johor. Reliability and regression are applied to determine the factors that affect the customer choice of conventional bank and the most influential factor between the three independent variables. Finding – The level of dependent variable is classified as moderate. Reliability, accessibility and convenience are found to have significant relationship toward affecting the customer choice of conventional bank. Reliability has the highest beta, thus it is the most influential factor that affect the customer choice of conventional bank.